Актуальные вопросы применения инновационных технологий в сфере специального и инклюзивного образования - Аслаева, Р. Г.; Сафонова, Т. В․
The article considered current issues of applying innovative technologies in the fi eld of special and inclusive education. Practice shows that technology for the design of educational correctional programs has priority; improvement of teaching facilities, creation of didactic materials to facilitate the assimilation of the curricula for students with special needs.
Keywords: Образование